Estudo de metodologias para avaliação do hormônio da paratireóide humano recombinante - Stamm, Fernanda Pavani (2013)
Human parathyroid hormone (hPTH) is a polypeptide with 84 amino acids and it is the most important peptide regulator for calcium and phosphate ion homeostasis, maintaining bone structure. Recombinant human parathyroid hormone, rhPTH (1-34), produced by DNA technology in Escherichia coli contain the active amino-terminal fragment of the full length hPTH and is currently being used worldwide for the treatment of osteoporosis at high risk of fractures in postmenopausal women and men with osteoporosis primary or hypogonadal. Reversed-phase liquid chromatography (RP-LC) and size exclusion liquid chromatography (SE-LC) methods were developed and validated for the assessment of recombinant human parathyroid hormone (rhPTH 1-34) in biopharmaceutical formulations. A gradient RP-LC method was carried out on a Zorbax 300 SB C18 column (150 mm x 4.6 mm i.d.), maintained at 40 ºC. The mobile phase A consisted of 0.1 M sodium sulphate buffer, pH 2.3, and the mobile phase B was acetonitrile. The SE-LC method was carried out on a BioSep-SEC-S 2000 column (300 mm x 7.8 mm i.d.), maintained at 25 ºC. The mobile phase consisted of 0.1 M phosphoric acid buffer, pH 2.5, run isocratically at a flow rate of 0.7 mL/min. Cromatographic separation was obtained with retention times of 12.2 min, and 13.2 min, and was linear over the concentration range of 1-250 μg/mL (r 2 = 0.9997) and 2-300 μg/mL (r 2 = 0.9993), respectively, for RP-LC and SE-LC, with photodiode array (PDA) detection at 214 nm. The limits of detection and quantitation were 0.44 and 1.47 μg/mL, respectively, for the RP-LC and 0.79 and 2.63 μg/mL, for the SE-LC. Specificity was established in degradation studies, which also showed that there was no interference of the excipients. Equally, the accuracy was 100.49% and 100.22%, with bias lower than 1.12% and than 0.81%. Moreover, the in vitro cytotoxicity test of related proteins and higher molecular weight forms showed significant differences (p< 0.05) compared to intact molecule. The validated methods were applied for the determination of rhPTH and related proteins in biotechnology-derived products, giving lower mean differences of the estimated content/potencies of 0.64% and 1.31% for the RP-LC and SE-LC related to the in vivo bioassay, and of 0.98% and 0.31% higher, compared to the in vitro cell culture assay, respectively. It is concluded that represents a contribution to establish new alternatives to monitor stability, quality control and thereby assure therapeutic efficacy of the biotechnology-derived medicine.